TNFR2 is required for RIP1-dependent cell death in human leukemia - Aguadé-Gorgorió, Júlia (Blood Adv, 2020)
Despite major advances in the treatment of patients with acute lymphoblastic leukemia in the last decades, refractory and/or relapsed disease remains a clinical challenge, and relapsed leukemia patients have an exceedingly dismal prognosis. Dysregulation of apoptotic cell death pathways is a leading cause of drug resistance; thus, alternative cell death mechanisms, such as necroptosis, represent an appealing target for the treatment of high-risk malignancies. We and other investigators have shown that activation of receptor interacting protein kinase 1 (RIP1)–dependent apoptosis and necroptosis by second mitochondria derived activator of caspase mimetics (SMs) is an attractive antileukemic strategy not currently exploited by standard chemotherapy. However, the underlying molecular mechanisms that determine sensitivity to SMs have remained elusive. We show that tumor necrosis factor receptor 2 (TNFR2) messenger RNA expression correlates with sensitivity to SMs in primary human leukemia. Functional genetic experiments using clustered regularly interspaced short palindromic repeats/Cas9 demonstrate that TNFR2 and TNFR1, but not the ligand TNF-α, are essential for the response to SMs, revealing a ligand-independent interplay between TNFR1 and TNFR2 in the induction of RIP1-dependent cell death. Further potential TNFR ligands, such as lymphotoxins, were not required for SM sensitivity. Instead, TNFR2 promotes the formation of a RIP1/TNFR1-containing death signaling complex that induces RIP1 phosphorylation and RIP1-dependent apoptosis and necroptosis. Our data reveal an alternative paradigm for TNFR2 function in cell death signaling and provide a rationale to develop strategies for the identification of leukemias with vulnerability to RIP1-dependent cell death for tailored therapeutic interventions.